Factors affecting quality of midwifery students learning in the workplace: Results of two ICM congress workshops. (July 2018) - Bharj, K.K.; Embo, M.
Highlights: The ICM's midwifery competencies and educational standards aims to strengthen midwifery education globally. The quality of workplace learning, assessment and supervision is critical in preparing midwives who are fit for practice. A wide range of factors affect the quality of workplace learning, assessment and supervision. Education organisations should implement focused interventions to promote workplace learning, assessment and supervision to prepare midwifery practitioners who can deliver safe and evidence based care to women and newborns. Abstract: At the 2014 and 2017 International Confederation of Midwives (ICM) conferences, members of the Practice Placements section of the Education Standing Committee (ESC) facilitated 'Education in Clinical Practice' workshops, attended by over 150 participants, reflecting low, middle and high income countries. The participants critically explored how workplace learning might be organised in pre-service midwifery curricula, ensuring achievement of clinical competencies recommended by the ICM and addressed the key issues encountered in providing quality of learning, assessment and supervision in workplace settings. This article discusses the key issues participants identified affecting student learning in the workplace.